Giant Enhancement of Spin‐Orbit Torque Efficiency in Pt/Co Bilayers by Inserting a WSe2 under Layer. (27th September 2021) - Xue, Hongwei; Tang, Meng; Zhang, Yu; Ji, Zhihao; Qiu, Xuepeng; Zhang, Zongzhi
Abstract: 2D transition metal dichalcogenides (TMDs) are excellent candidate materials to study the effect of spin‐orbit torques (SOTs). Here, the effect of a WSe2 underlayer on the magnetic properties and SOT efficiencies are systematically investigated in Pt /Co bilayers with perpendicular magnetic anisotropy. SOT efficiency ξ shows an increasing trend as the inserted WSe2 monolayer number increases from 0 to 5, which is attributed to the elevated spin absorption at the WSe2 /Pt interface where WSe2 acts as a spin sink. As the Co layer thickness t Co increases from 0.6 to 1.0 nm, ξ exhibits a maximum at t Co  = 0.8 nm, which is mainly due to the nonmonotonic change of spin transmission at the Pt/Co interface. Moreover, the ξ value of WSe2 (5ML) /Pt/Co increases significantly when the measurement temperature decreases, which can be interpreted by the increased spin absorption capability of WSe2 due to the elevated spin mixing conductance at reduced temperatures. The findings provide deep insight into the origin of robust charge‐spin conversion in the TMD/Pt/Co system, which will promote the implementation of advanced SOT devices based on the 2D materials. Abstract : A comprehensive investigation on the magnetic and transport properties are performed in a perpendicularly magnetized WSe2 /Pt/Co/AlOx heterostructures. SOT efficiency ξ increases with the thickness of WSe2, suggesting that WSe2 serves as a good spin sink. Moreover, ξ is found to increase rapidly with the decreased temperature for WSe2 /Pt/Co as a result of the enhanced interfacial spin transparency.